( a 5 + b 5 + c 5 ) 2 ( a 3 + b 3 + c 3 ) 2 ( a 4 + b 4 + c 4 )
Given a , b and c satisfy a + b + c = 0 and a 5 + b 5 + c 5 = 0 , the value of the above expression can be expressed as n m , where m and n are coprime positive integers , calculate the value of m + n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Using Newton sum.
Firstly finding ( a 3 + b 3 + c 3 ) .
a
3
+
b
3
+
c
3
=
(
a
+
b
+
c
)
(
a
2
+
b
2
+
c
2
)
−
(
a
b
−
b
c
−
c
a
)
(
a
+
b
+
c
)
+
3
a
b
c
a
3
+
b
3
+
c
3
=
3
a
b
c
⇒
(
a
3
+
b
3
+
c
3
)
2
=
9
(
a
b
c
)
2
Secondly finding ( a 4 + b 4 + c 4 ) .
a
4
+
b
4
+
c
4
=
(
a
2
+
b
2
+
c
2
)
2
−
2
[
(
a
b
)
2
+
(
b
c
)
2
+
(
c
a
)
2
]
a
4
+
b
4
+
c
4
=
[
(
a
+
b
+
c
)
2
−
2
(
a
b
+
b
c
+
c
a
)
]
−
2
[
(
a
b
)
2
+
(
b
c
)
2
+
(
c
a
)
2
]
⇒
a
4
+
b
4
+
c
4
=
2
[
(
a
b
)
2
+
(
b
c
)
2
+
(
c
a
)
2
]
Thirdly finding ( a 5 + b 5 + c 5 ) .
a
5
+
b
5
+
c
5
=
(
a
+
b
+
c
)
(
a
4
+
b
4
+
c
4
)
−
(
a
b
+
b
c
+
c
a
)
(
a
3
+
b
3
+
c
3
)
+
a
b
c
(
a
2
+
b
2
+
c
2
)
a
5
+
b
5
+
c
5
=
(
a
b
+
b
c
+
c
a
)
(
−
5
a
b
c
)
⇒
(
a
5
+
b
5
+
c
5
)
2
=
(
a
b
+
b
c
+
c
a
)
2
(
−
5
a
b
c
)
2
=
[
(
a
b
)
2
+
(
b
c
)
2
+
(
c
a
)
2
]
(
−
5
a
b
c
)
2
⟹ ( a 5 + b 5 + c 5 ) 2 ( a 3 + b 3 + c 3 ) 2 ( a 4 + b 4 + c 4 )
⇒ [ ( a b ) 2 + ( b c ) 2 + ( c a ) 2 ] × 2 5 ( a b c ) 2 9 ( a b c ) 2 × 2 [ ( a b ) 2 + ( b c ) 2 + ( c a ) 2 ]
⇒ 2 5 1 8 = n m
⇒ m + n = 1 8 + 2 5 = 4 3
Or put a = 2 , b = − 1 , c = − 1 .. :-p....BTW (+1)
Problem Loading...
Note Loading...
Set Loading...
Using Newton's sums method and let P n = a n + b n + c n , where n is a positive integer, S 1 = a + b + c = 0 , S 2 = a b + b c + c a , and S 3 = a b c . Then, we have:
\(\begin{array} {} P_1 = S_1 & = 0 & = 0 \\ P_2 = S_1P_1 - 2S_2 & = 0 - 2 S_2 & = - 2S_2 \\ P_3 = S_1P_2 - S_2P_1 + 3S_3 & = 0 - 0 + 3S_3 & = 3S_3 \\ P_4 = S_1P_3 - S_2P_2 + S_3P_1 & = 0 - S_2(-2S_2) + 0 & = 2S_2^2 \\ P_5 = S_1P_4 - S_2P_3 + S_3P_2 & = 0 - S_2(3S_3) + S_3(-2S_2) & = -5S_2S_3 \end{array} \)
⟹ ( a 5 + b 5 + c 5 ) 2 ( a 3 + b 3 + c 3 ) 2 ( a 4 + b 4 + c 4 ) = P 5 2 P 3 2 P 4 = ( − 5 S 2 S 3 ) 2 ( 3 S 3 ) 2 ( 2 S 2 2 ) = 2 5 1 8
⟹ m + n = 1 8 + 2 5 = 4 3